2019
DOI: 10.1002/adhm.201801313
|View full text |Cite
|
Sign up to set email alerts
|

Oil Core–PEG Shell Nanocarriers for In Vivo MRI Imaging

Abstract: Oil‐in‐water emulsions represent a promising carrier for in vivo imaging because of the possibility to convey poorly water‐soluble species. To promote accumulation at the tumor site and prolong circulation time, reduction of carrier size and surface PEGylation plays a fundamental role. In this work a novel, simple method to design an oil‐core/PEG‐shell nanocarrier is reported. A PEG‐shell is grown around a monodisperse oil‐in‐water nanoemulsion with a one‐pot method, using the radical polymerization of poly(et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…[177] PEG shell at the NEs surface was also introduced using a radical polymerization of poly(ethylene glycol)diacrylate, and the oil core-PEG shell NEs were successfully loaded with lipophilic contrast agents, such as iron oxide nanocubes and fluorescent dye indocyanine green. [178]…”
Section: Surface Modification Of Nesmentioning
confidence: 99%
“…[177] PEG shell at the NEs surface was also introduced using a radical polymerization of poly(ethylene glycol)diacrylate, and the oil core-PEG shell NEs were successfully loaded with lipophilic contrast agents, such as iron oxide nanocubes and fluorescent dye indocyanine green. [178]…”
Section: Surface Modification Of Nesmentioning
confidence: 99%
“…After, 20.83 mg of CUR was added to the mixture [38]. The final emulsion was obtained by adding 19.3 mL of Milli-Q water to oil phase [34]. After the process, 100 µL of CUR-NE was used to produce CUR-NE-MPs as described in the previous paragraph.…”
Section: Cur-o/w 20% Oil Nano-emulsion (Cur-ne) As Water Phasementioning
confidence: 99%
“…We decided to use curcumin since it is a powerful active substance by itself (ex. anti-inflammatory [33,34], anticancer [33]) and a hydrophobic molecule with a logP value of~3.0, which allows it to be dissolvable in common organic solvents and partially soluble in polar solvents including water [35]. These characteristics are common to many hydrophobic drugs (prostaglandin, doxorubicin) making curcumin an ideal model drug.…”
Section: Introductionmentioning
confidence: 99%
“…Among the diagnostic techniques available at present, photoacoustic imaging (PAI) is a non-invasive diagnostic tool which provides high sensitivity and helps overcoming the limited depth penetration and spatial resolution of the conventional optical imaging (Wang and Hu, 2012). In order to increase the image contrast when using this technique, nanoparticles have been successfully employed as contrast agent material (Calcagno et al, 2019). Qin et al (2018) recently reported the use of NPs composed by a semiconductor polymeric contrast agent (PCPDTBT) encapsulated in a FDA approved lipid-based copolymer (DSPE-PEG-Maleimide).…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%